2011
DOI: 10.1063/1.3652705
|View full text |Cite
|
Sign up to set email alerts
|

Efficient laser-proton acceleration from an insulating foil with an attached small metal disk

Abstract: Efficient proton acceleration by the interaction of an intense femtosecond laser pulse with a solid foil has been demonstrated. An aluminum coating (thickness: 0.2 μm) on a polyethylene (PE) foil was irradiated at 2 × 1018 W/cm2 intensity. The protons from the aluminum-disk (diameter: 150 μm to 15 mm) foil were accelerated to much higher energy in comparison with conventional targets such as PE and aluminum-coated PE foils. The fast electron signal along the foil surface was significantly higher from the alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that cone-wire targets [8], sandwiched targets [9], and underdense targets [10] can efficiently transport energetic electrons over distances of about 1 mm, and fine wire targets can transport electrons as far as 1 m [ 11 ]. It has also been ob served that laser-accelerated ions are generated at distances up to a few millimeters away from the laser-irradiated region [12], and that the maximum proton energy is increased by using disk targets with a diameter of a few millimeters [13], Therefore, it is essential to observe and understand the dynamics of fast electrons, and the electromagnetic fields that they induce, over a large region (on the order of several millimeters) outside the laser-irradiated region for various materials. This could aid the development of efficient laser-induced plasma radiation sources for many attractive applications, including fast ignition for inertial confinement fusion [14,15], ultrafast electron diffraction measurements [16,17], time-resolved x-ray probes [18,19], laser-driven nuclear physics [20], and tumor therapy using ion beams [21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that cone-wire targets [8], sandwiched targets [9], and underdense targets [10] can efficiently transport energetic electrons over distances of about 1 mm, and fine wire targets can transport electrons as far as 1 m [ 11 ]. It has also been ob served that laser-accelerated ions are generated at distances up to a few millimeters away from the laser-irradiated region [12], and that the maximum proton energy is increased by using disk targets with a diameter of a few millimeters [13], Therefore, it is essential to observe and understand the dynamics of fast electrons, and the electromagnetic fields that they induce, over a large region (on the order of several millimeters) outside the laser-irradiated region for various materials. This could aid the development of efficient laser-induced plasma radiation sources for many attractive applications, including fast ignition for inertial confinement fusion [14,15], ultrafast electron diffraction measurements [16,17], time-resolved x-ray probes [18,19], laser-driven nuclear physics [20], and tumor therapy using ion beams [21 ].…”
Section: Introductionmentioning
confidence: 99%